2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41
Combine like terms: -2x - 4y + 5x - 7y = 3x - 11y -2x + 5x = 3x -4y + -7y = -11y
x = 4 and y = 0
2x + 4y - 5x + 3y = 7y - 3x
the system of equations 3x-6y=20 and 2x-4y =3 is?Well its inconsistent.
They are: x = -2 and y = -1.
3x + 7y
2x + 4y = 16 is the same as 4y = -2x + 16 divide both sides by 4 and you get y = (-x/2) +4 3x - 2y = 6 is the same as -2y = -3x + 6 divide both sides by 2 and you get y = (-3x/2) + 3 therfore they do not have the same solution
This simplifies to 3x-6+4y.
In its simplest form: 2y -5x
Y = 1/2x + 2
4y = 3x+11 or as y = 3/4x+11/4
2x = 3x - 4y - 16 so 4y = x - 16 or y = x/4 - 4 Slope = 1/4 or 0.25 intercept = -16
2x+3xy-4y=10to solve for yyour objective will be to get y by itself on one side of the equal signyou first subtract 2x to get the terms with y variables on one side3xy-4y=10-2xthen undistribute the y from the two terms to get one yy(3x-4)=10-2xnow divide 3x-4y=(10-2x)/(3x-4)theres your answer
2x+4y = -8 4y = -2x-8 y = -1/2x-2 or y = -0.5x-2
if you rearrange it, it becomes 4y + 8 = 3x2 -2x +1 4y = 3x2 -2x -7 y= (3x2 -2x -7)/4 which is a parabola
It is a straight line equation.
It is: 3x+4y which is an algebraic expression